Current State of Research on the Development Methodology of Co-created Products and Products with Personality - Teodora-Iustina TUDOR; Nicolae IONESCU (Communications of International Proceedings, 2021)
Numerous methodologies have been developed over time to improve the design of products in order to fulfill the wishes and expectations of customers, but so far none of these methodologies has been directly contributing to the design process of products ensuring guaranteed success. This is difficult to achieve due to various aspects related to the human personality that is influenced by one's own life experience, the process of transposing characteristics of human personality to a product in the design and anticipating how the market will evolve, given the socio-economical context. Although input from consumers about how they relate to a product's personality is important, the influence of personality on purchasing preferences and how they interact is only a basis for designers and manufacturers to help them approach the consumer's desire, without knowing with certainty their desire or whether the product will be successful or not. In this situation, more research is necessary to attain the design of a generally valid methodology for a wide variety of products.
Keywords: Product with Personality; Co-Created Products; Design; Emotions; Methodology